Mobile Loyalty Application Development Based on Android - Angela Irina; Megawati Megawati; Abednego Abednego; Natalia Chandra; Irma Kartika Wairooy; Alvina Aulia (Bina Nusantara University, 2016)
The research objective is to develop an application that allows users to participate in a loyalty program and facilitate Smartphone enterprise (Merchant) in access, sale and observation of customer transactions through mobile applications. Design method used is object-based design that includes a UML of use case diagrams, use case narrative, class diagram, sequence diagrams and activity diagrams. Results achieved in the form of mobile applications that are able to facilitate customer in managing loyalty cards as well as to increase customer loyalty. This application features, such as add points, redeem, news, transaction history, and message that can facilitate customer in managing customer loyalty card. The conclusion of this design is that the application of E Points can enable customers to manage a loyalty card in Smartphone, add points, redeem rewards, obtain the latest promotional information through news features, and view transaction history.